Municipal decentralisation and governance: Autonomy, accountability and participation - Mohanty, Prasanna K. (1995)
In 74th Constitutional Amendment Act, the author analyses in detail the provisions made in conformity legislations enacted at State/UT levels on three most important aspects - functional and financial decentralisation, and popular participation and points out their drawbacks. He then examines how these provisions address three fundamental issues of political decentralisation, i.e. autonomy, accountability and participation. To identify municipal decentralisation process, the author explains the allocation of expenditure, revenue assignment and intergovernmental transfers in a federal system of today
Keywords: Decentralization in government - India; India - Constitution - Amendments - 74th; Municipal government - India; Local government - India; Local government